Activation of remaining key enzymes in dried under-fermented cocoa beans and its effect on aroma precursor formation - Selamat, Jinap; Saari, Nazamid; Bakar, Jamilah; ., Misnawi (Elsevier, 2002)
Incubation-activation of remaining key enzymes in dried under-fermented cocoa beans and its effect on aroma precursor formation has been studied using defatted unfermented and partly fermented cocoa bean powders. Results of the study showed that aspartic endoprotease, carboxypeptidase and invertase were significantly inactivated during fermentation and drying, and the effect of fermentation was significantly lower than that of drying. The enzyme activities remaining in these beans were still sufficient to carry out enzymatic reaction during incubation. Peptide patterns, resulting from incubation of unfermented and partly fermented beans powders, were quite similar to the well-fermented patterns. Meanwhile, free amino acid concentrations of the unfermented beans were significantly increased during the first 4 h of incubation and then remained constant; however, with partly fermented beans, the formation continued and the hydrophobic and total free amino acid concentrations reached the value of well-fermented beans after 24 h of incubation. Reducing sugar concentrations of both unfermented and partly fermented cocoa beans could reach the level of well-fermented beans by incubation.